Efektivitas Media Video Tutorial dalam Meningkatkan Kemandirian Anak Disabilitas Intelektual Sedang - Nur’aini, Nur’aini; Zulmiyetri, Zulmiyetri; Rahmatrisilvia, Rahmatrisilvia; Safaruddin, Safaruddin (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study focuses on a child with moderate intellectual disability in class X of SMALB Wacana Asih Padang, who is not yet able to independently make palm sugar milk coffee and still requires guidance from teachers. The objective is to evaluate the effectiveness of Video tutorials in improving the child's independence. Using a quantitative approach and a Single Subject Research (SSR) design with an A-B-A model, this study involved one subject. The data showed an increase in FH's independence from a score of 29 in the initial baseline condition (A1) to 71, 86, and 100 in the intervention condition (B), and remained at 100 in the follow-up baseline condition (A2). The analysis results indicate that tutorial videos are effective in improving the independence of children with moderate intellectual disabilities.